Titian's man in a red hat - Dalvit, Giulio; Peyton, Elizabeth 1965- (The Frick Collection, 2022)
"Focusing on Titian's "Man in a Red Hat," the latest volume in the Frick Diptych series pairs an essay by Giulio Dalvit, Assistant Curator of Sculpture at The Frick Collection, with a contribution by the contemporary artist Elizabeth Peyton"-- Zählung der Serie dem Vorwort entnommen
Keywords: Vecellio, Tiziano -- 1477-1576 -- Portrait of a man in a red hat; Frick Collection; Titian / approximately 1488-1576 / Criticism and interpretation; Portraits, Renaissance / Italy; Titian / approximately 1488-1576; Portraits, Renaissance; Italy; Criticism, interpretation, etc